2022
DOI: 10.3390/agriculture12040561
|View full text |Cite
|
Sign up to set email alerts
|

Design and Key Parameter Optimization of Conic Roller Shelling Device Based on Walnut Moisture-Regulating Treatments

Abstract: The quality of walnuts deteriorates owing to the poor quality of the shelling equipment. The improvement of shelling quality is urgently required for walnut processing. In this study, systematic research was carried out on the changes in walnut mechanical properties, mechanical model of walnut shelling, and the key parameters of the equipment. The key parameters were determined as the angles of the shelling conic roller (X1), speeds of the shelling conic roller (X2), clearance between the shelling conic roller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the harvest season of 2021, fresh-harvested walnuts (Juglans regia L.) were collected from the Wensu Walnut Experimental Station (latitude: 41 • 27 67 N, longitude: 80 • 24 17 E, and at a 1056 m altitude), Xinjiang, China. A moderate walnut moisture content is known to improve the quality of cracking [17]. Thus, according to our previous study [18], walnut shells with a moisture content range of 7-9% and kernels with a moisture content range of 10-13% were used in the walnut cracking experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the harvest season of 2021, fresh-harvested walnuts (Juglans regia L.) were collected from the Wensu Walnut Experimental Station (latitude: 41 • 27 67 N, longitude: 80 • 24 17 E, and at a 1056 m altitude), Xinjiang, China. A moderate walnut moisture content is known to improve the quality of cracking [17]. Thus, according to our previous study [18], walnut shells with a moisture content range of 7-9% and kernels with a moisture content range of 10-13% were used in the walnut cracking experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The length (L), width (W), and thickness (T) [17] of 200 randomly selected walnuts were measured (Figure 2) using a DELI DL91150 digital caliper (DELI Group Co., Ltd., Ningbo, China) with an accuracy of 0.01 mm. To classify the walnuts more accurately, the equivalent diameter of walnut samples was calculated based on Equation (1) mentioned in Zeng et al [19] and the statistical results are shown in Figure 3.…”
Section: Design Of Grading Cylindermentioning
confidence: 99%
“…Both domestic and international scholars have conducted extensive research on walnut shell‐breaking methods (Ding et al, 2017; Wang et al, 2022; Zhang et al, 2018). Most research outcomes are concentrated on traditional single‐shell methods or their improvements, overlooking the study of combining various shelling methods (Barakaev et al, 2021; Cao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to high domestic processing costs, even walnuts cultivated in developed countries such as France are exported to Moldova for shelling and then reimported to minimize the walnut processing costs (CBI 2019). Thus, sustainable valorizing of walnut shells (WS) can help, to an extent, in offsetting the cost of shelling which itself is a complex and resource-intensive process (Wang et al 2022).…”
Section: Introductionmentioning
confidence: 99%